1995
DOI: 10.1136/ard.54.12.983
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II genes associated with anticentromere antibody in Japanese patients with systemic sclerosis (scleroderma).

Abstract: Objective-To define further HLA class II gene associations with anticentromere antibody (ACA), a major serum antinuclear antibody in patients with systemic sclerosis (SSc). Methods-HLA class II genes were determined using polymerase chain reaction/ restriction fragment length polymorphisms in 94 Japanese patients with SSc (22 ACA positive and 72 ACA negative) and 50 race matched normal control subjects. Results-Frequency of DQBI*0501 was increased in ACA positive SSc patients compared with ACA negative SSc pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 19 publications
5
25
1
Order By: Relevance
“…Previous studies investigated the association of HLA genotyping with disease susceptibility in ACApositive patients. A high frequency of the HLA-DQB1*0501 or DRB1*0101 alleles in Japanese patients with ACApositive SSc was reported (12,13), whereas none of the patients in the present study had them. Furthermore, though HLA-DRB1*0803 is reportedly associated with the development of PBC in Japanese (14), the gene was present in only 1 patient (Patient 5) who was asymptomatic but had positive anti-mitochondrial antibodies.…”
Section: Discussioncontrasting
confidence: 60%
“…Previous studies investigated the association of HLA genotyping with disease susceptibility in ACApositive patients. A high frequency of the HLA-DQB1*0501 or DRB1*0101 alleles in Japanese patients with ACApositive SSc was reported (12,13), whereas none of the patients in the present study had them. Furthermore, though HLA-DRB1*0803 is reportedly associated with the development of PBC in Japanese (14), the gene was present in only 1 patient (Patient 5) who was asymptomatic but had positive anti-mitochondrial antibodies.…”
Section: Discussioncontrasting
confidence: 60%
“…Anti-topo I antibodies are characteristic of the diffuse type of SSc (1,120). The possibility that an autoantigen elicits both an autoantibody response and a cellular response is supported by the findings of a substantially stronger HLA association with autoantibody profiles than with the disease itself (64)(65)(66)(67)(68)140). Kuwana et al reported that HLA-DQ and DR genes together control the anti-topo I antibody response in patients with SSc (68).…”
Section: Putative T Cell Antigens In Sscmentioning
confidence: 48%
“…Antibodies to CENP-E, a centromere kinesin-like protein, are found mostly in a rather infrequent form of SSc known as the CREST syndrome (calcinosis, Raynaud's phenomenon, esophageal dysmotility, sclerodactyly, telangiectasias), and their presence is associated with the HLA-DQB1*05 alleles (121). Certain HLA-DRB1 (DRB1*0101,*0405, and *01302) or DQB1 (DQB1*0501) alleles were found to be associated with high serum anticentromere titers (140).…”
Section: Putative T Cell Antigens In Sscmentioning
confidence: 99%
“…Hence, most of the strongest associations are found within the major autoantibody positive subgroup of patients ( Table 2). The most solid, replicated associations with the autoantibody subgroups are the HLA-DQB1*0501/HLA-DRB1*0101 haplotype with the production of ACA (Arnett et al 2010;Simeon et al 2009;Kuwana et al 1999;Kuwana et al 1995), HLA-DRB1*1104 and HLA-DPB1*1301 with the production of ATA (Simeon et al 2009;Gilchrist et al 2001;Fanning et al 1998) and HLA-DQB1*0302 with the production of ARA (Arnett et al 2010;Kuwana et al 1999). It is noteworthy that the Wrm association of the absence of a polar aminoacid in the position 26 of the HLA-DQB1 molecule with the presence of ACA which has been only found in populations of Caucasian origin (Arnett et al 2010;Gilchrist et al 2001;McHugh et al 1994;Beretta et al 2011).…”
Section: Hla Genesmentioning
confidence: 96%